INDONESIAN ENTREPRENEUR'S BAROMETER 2004 ( SECOND PAPER OF TWO ) - Arnold, John; Waworuntu, Rossy; Mangkusubroto, Kuntoro; Tjakraatmadja, Jann Hidajat; Dhewanto, Wawan (SBM ITB, 2005)
This year, for the first time, Ernst & Young Indonesia and School of Business and Management (SBM), Bandung Institute of Technology (ITB) conducted Indonesian Entrepreneursâ?? Barometer survey. This first Indonesian Entrepreneurâ??s Barometer, surveyed Indonesian entrepreneur to get the views of entrepreneurs who are qualified as outstanding amongst their peers. Survey respondents were selected by Ernst & Young Indonesia panels. The survey covers motivations, future plans and perceptions about Indonesian business environment. The results are presented in 4 chapters under the following title: â?? Succesful Entrepreneurs and their Businessâ?, â?? Funding & Wealth Realizationâ?, â?? Entrepreneurâ??s Outlookâ? and â?? Business Environmentâ?. The second paper covers the last two chapters.